High-speed X-ray radiography for experiments in impact dynamics using high-power X-ray tube, cesium iodine scintillator and laboratory optical camera - Jan Šleichrt; Jan Falta; Tomáš Fíla (Acta Polytechnica CTU Proceedings, 2023)
X-ray radiography and computed tomography have become well-established methods for investigation of internal structure of objects and for defectoscopy. Recently, the methods have even been used for in-situ analysis of materials under mechanical loading. Although the techniques would be very suitable for analysis during dynamic events, their application is constrained by typical achievable frame rates. Therefore, fast imaging is usually limited to facilities providing sufficient flux like particle accelerators. In this paper, we test imaging performance of a laboratory-based setup with a high-power X-ray tube, a scintillation panel, and an optical camera. Fast-rotating object and typical specimens for impact testing are irradiated with different power settings and quality of captured images is evaluated and analyzed. It is found out that the system can be successfully used for imaging at several hundred frames per second allowing for inspection of slow impact dynamics experiments.